2014
DOI: 10.1159/000368893
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Sulfoxide Reductase A, B1 and B2 Are Likely to Be Involved in the Protection against Oxidative Stress in the Inner Ear

Abstract: The methionine sulfoxide reductase (Msr) family of proteins is a class of repair enzymes that reduce methionine-S (MsrA) or methionine-R (MsrB) sulfoxide to methionine. Recent studies have reported that mutations in the MSRB3 gene cause autosomal recessive hearing loss in humans, and in mice MsrB3 deficiency leads to profound hearing loss due to hair cell apoptosis and stereocilia degeneration. However, apart from MsrB3, studies on Msr proteins in the inner ear have not yet been reported. In this study, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…The expression of MsrB1 in the outer and inner hair cells of the Corti organ and in the spiral ganglion suggests a possible role of MsrB1 in the protection from cochlear oxidative stress [Kwon et al, 2014b]. In this study, we observed that MsrB1 expression in young MsrA knockout mice was similar to that of young wild-type mice (Fig.…”
Section: Mechanisms Of Msr-mediated Protection In the Inner Earsupporting
confidence: 65%
See 3 more Smart Citations
“…The expression of MsrB1 in the outer and inner hair cells of the Corti organ and in the spiral ganglion suggests a possible role of MsrB1 in the protection from cochlear oxidative stress [Kwon et al, 2014b]. In this study, we observed that MsrB1 expression in young MsrA knockout mice was similar to that of young wild-type mice (Fig.…”
Section: Mechanisms Of Msr-mediated Protection In the Inner Earsupporting
confidence: 65%
“…The MsrA gene has a role in supporting the cells linked to the spiral ligaments and spiral ganglion neurons [Kwon, et al 2014b]. Our current study indicates that young MsrA knockout mice consist of high-frequency threshold elevation for distortion product otoacoustic emission (DPOAE) and auditory brainstem response (ABR), which usually gets worse by 6 months of age.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Oxidative stress‐induced methionine sulfoxidation is recognized to modify diverse proteins, altering function, and potentially leading to disease (Gu et al , ) [calmodulin (Gao et al , ), thrombomodulin (Glaser et al , ), CaMKII (Erickson et al , )]. The methionine sulfoxide reductase family can reverse such protein damage (MsrA, B1, B2, and B3) (Marchetti et al , ; Cabreiro et al , ; Kwon et al , ), serving a protective role in all cells including blood cells (Rosen et al , ; Ouseph et al , ). Distinct from MsrA (mitochondria, cytosol, and nucleus), MsrB1 (cytosol and nucleus), and MsrB3 (ER and mitochondria), all localized to multiple cellular compartments, MsrB2 is located only in the mitochondrial matrix (Yermolaieva et al , ; Fischer et al , ).…”
Section: Discussionmentioning
confidence: 99%